Influence of local production and vertical transport on the organic aerosol budget over Paris. Issue 15 (3rd August 2017) - Janssen, R. H. H.; Tsimpidi, A. P.; Karydis, V. A.; Pozzer, A.; Lelieveld, J.; Crippa, M.; Prévôt, A. S. H.; Ait‐Helal, W.; Borbon, A.; Sauvage, S.; Locoge, N.
Abstract: We performed a case study of the organic aerosol (OA) budget during the MEGAPOLI campaign during summer 2009 in Paris. We combined aerosol mass spectrometer, gas phase chemistry, and atmospheric boundary layer (ABL) data and applied the MXL/MESSy column model. We find that during daytime, vertical mixing due to ABL growth has opposing effects on secondary organic aerosol (SOA) and primary organic aerosol (POA) concentrations. POA concentrations are mainly governed by dilution due to boundary layer expansion and transport of POA‐depleted air from aloft, while SOA concentrations are enhanced by entrainment of SOA‐rich air from the residual layer (RL). Further, local emissions and photochemical production control the diurnal cycle of SOA. SOA from intermediate volatility organic compounds constitutes about half of the locally formed SOA mass. Other processes that previously have been shown to influence the urban OA budget, such as aging of semivolatile and intermediate volatility organic compounds (S/IVOC), dry deposition of S/IVOCs, and IVOC emissions, are found to have minor influences on OA. Our model results show that the modern carbon content of the OA is driven by vertical and long‐range transport, with a minor contribution from local cooking emissions. SOA from regional sources and resulting from aging and long‐lived precursors can lead to high SOA concentrations above the ABL, which can strongly influence ground‐based observations through downward transport. Sensitivity analysis shows that modeled SOA concentrations in the ABL are equally sensitive to ABL dynamics as to SOA concentrations transported from the RL. Key Points: Boundary layer dynamics have opposing effects on POA (dilution) and SOA (enrichment) concentrations over Paris SOA from intermediate volatility organic compounds constitutes about half of the locally formed SOA mass Modeled SOA concentrations are equally sensitive to ABL dynamics as to SOA concentrations above the ABL